2020
DOI: 10.1080/10298436.2020.1806278
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative aging of epoxy asphalt

Abstract: Oxidative aging is responsible for the irreversible asphalt stiffening and embrittlement leading to asphalt pavements of increased susceptibility to fatigue and thermal cracking. In recent years, various flexible binders have been introduced in asphalt industry to produce long-life pavements and the epoxy asphalt binders are among them. Nevertheless, in-depth understanding of the oxidative aging mechanism of epoxy asphalt binders and binding systems is still needed to enable reliable predictions of material de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Sulfoxide compound contents were showed to be the most effective parameter for the evaluation of oxidative-controlled curing for EA [58]. In addition, a period of rapid decrease of carbonyl and sulfoxide compounds under isothermal oxidation conditioning indicated epoxy curing, whereas a period of constant increase of both compounds after curing indicated oxidative aging [125].…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
“…Sulfoxide compound contents were showed to be the most effective parameter for the evaluation of oxidative-controlled curing for EA [58]. In addition, a period of rapid decrease of carbonyl and sulfoxide compounds under isothermal oxidation conditioning indicated epoxy curing, whereas a period of constant increase of both compounds after curing indicated oxidative aging [125].…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
“…Epoxy-asphalt binder is a type of thermosetting binder designed for flexible pavements. Despite the inherently brittle and poorly cracking resistant thermosetting epoxy resins, this binder cures to a rubbery system (Apostolidis et al, 2020b;Herrington & Alabaster, 2008;Kang et al, 2010;Luo et al, 2015;Widyatmoko et al, 2006;Xiao et al, 2011;Youtcheff et al, 2006). Shell Oil Company originally developed the epoxy-asphalt binder in the 1960s as a material with superior resistance to jet fuel damage.…”
Section: Introductionmentioning
confidence: 99%
“…The epoxy-asphalt binder, or epoxy binder, has been diluted with a conventional bitumen to balance the cost and performance. This idea has been already adopted as well as a feasible method to produce epoxy materials under longer operational time windows (Apostolidis et al, 2018(Apostolidis et al, , 2020a(Apostolidis et al, , 2020bApostolidis, Liu, van de Ven, et al, 2019;Herrington & Alabaster, 2008;Huang et al, 2020;Wu et al, 2017;Yao et al, 2019). Laboratory studies indicated a significant decrease in stiffness and elasticity of epoxy-asphalt materials could be obtained by reducing the proportion of epoxy binder in bitumen (Apostolidis et al, 2020b;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many studies have focused on anti-ageing to find lasting solutions for thermochemical stability [ 14 , 16 ]. One of the modern solutions is the introduction of epoxy-based compounds as anti-ageing technologies for bituminous materials [ 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%